PENGARUH KOMPETENSI AUDITOR, TEKANAN ANGGARAN WAKTU DAN KOMPLEKSITAS AUDIT TERHADAP KUALITAS AUDIT DENGAN PEMAHAMAN SISTEM INFORMASI SEBAGAI VARIABEL MODERATING (Studi Empiris pada Inspektorat Daerah Se Provinsi Banten) - Yuliyanti, Yeli Sita; Hanifah, Imam Abu (JURNAL RISET AKUNTANSI TIRTAYASA, 2018)
This study aims to examine the effect of auditor competence, time budget pressure and audit complexity on audit quality with an understanding of information systems as a moderator in Banten Province Inspectorate. The population in this study were the auditors who worked as examiners throughout the Inspectorate throughout Banten Province totaling 338 people, taking samples using purposive sampling method as many as 175 people. The source of this research data is primary data which is obtained from the distribution of questionnaires to the research respondents. The data in this study were analyzed using Structural Equation Model (SEM) using the Partial Least Square (PLS) approach and using the smart PLS 3.0 analysis tool. The test results show that auditor competence and time budget pressure have a positive effect on audit quality, while audit complexity has a negative effect on audit quality. In addition, understanding of information systems can moderate the influenceof competence on audit quality, while understanding information systems cannot moderate the influence of time budget pressure and audit complexity on audit quality. Keywords: auditor competency, time budget pressure, audit complexity, audit quality, understanding of information systems